2023
DOI: 10.1002/advs.202301098
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Ultralow‐Pt‐Loading Electrocatalysts for the Efficient Hydrogen Evolution

Abstract: Hydrogen production from water electrolysis provides a green and sustainable route. Platinum (Pt)-based materials have been regarded as efficient electrocatalysts for the hydrogen evolution reaction (HER). However, the large-scale commercialization of Pt-based catalysts suffers from the high cost. Therefore, ultralow-Pt-loading electrocatalysts, which can reach the balance of low cost and high HER performance, have attracted much attention. In this review, representative promising synthetic strategies, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 151 publications
0
26
0
Order By: Relevance
“…Currently, noble metal materials are dominating as the benchmark electrodes for HER. 4 For example, Lin et al 5 reported that RuO 2 /NiRu exhibited a Tafel slope of 33 mV dec −1 and an overpotential of 13 mV to reach a current density of 10 mA cm −2 for HER. Nevertheless, the high price and scarcity of these noble metals seriously impede their application.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, noble metal materials are dominating as the benchmark electrodes for HER. 4 For example, Lin et al 5 reported that RuO 2 /NiRu exhibited a Tafel slope of 33 mV dec −1 and an overpotential of 13 mV to reach a current density of 10 mA cm −2 for HER. Nevertheless, the high price and scarcity of these noble metals seriously impede their application.…”
Section: Introductionmentioning
confidence: 99%
“…At present, steam methane reforming (SMR) is the main industrial hydrogen production method, and it consumes a large amount of CH 4 during this process. , So, it cannot achieve absolute green energy from the source. The hydrogen evolution reaction (HER), using highly active catalytic electrodes to achieve low overpotential hydrogen production, has realized efficient electrolysis of commercial hydrogen production. Up to now, the Pt is commonly recognized as the highly efficient HER catalyst with wide applications . However, high cost and scarcity hinder the massive use of Pt in industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…4−9 Up to now, the Pt is commonly recognized as the highly efficient HER catalyst with wide applications. 10 However, high cost and scarcity hinder the massive use of Pt in industrial production. Therefore, the search for novel HER catalysts that balance high efficiency and low cost has aroused the interest of a large number of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…4–6 At present, expensive platinum-group noble metals have been established as the most effective HER electrocatalysts with extremely high catalytic activity and low overpotentials. 7–9 However, high cost and low availability restrict their widespread application. 10,11 Therefore, it is necessary to design efficient alternative HER electrocatalysts based on nonprecious metals.…”
Section: Introductionmentioning
confidence: 99%